Efektivitas Internal Control over Financial Reporting (ICFR) pada project konstruksi perusahaan BUMN karya - Farradhi, Muhammad; Hartanti, Dwi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study explores how the BUMN Karya Company's building project team in Aceh implemented Internal Control over Financial Reporting (ICFR). This research is based on the many incidents of building project fraud by corporations, which affects financial statements that cannot provide peace of presentation. This study uses case studies and descriptive analysis to measure ICFR effectiveness using the Guidance for Smaller Public Companies Reporting on Internal Control over Financial Reporting (2006) and the COSO Framework. Interviews and BUMN Karya project team business process documents provided research data. The study concluded that the deployment of ICFR in three important business processes of the company based on withdrawals discovered two BUMN Karya project team business processes with an ICFR evaluation in the material weekness category and one in the control deficiency category. The investigation shows that the project construction team's business processes need modification for credible financial reports. Thus, this research can contribute to ICFR literature to ensure financial report secrecy.